Combining CGM and an Online Peer Support Community for Hispanic Adults with T2D: A Feasibility Study. (July 2022) - Litchman, Michelle L.; Ng, Ashley; Sanchez-Birkhead, Ana; Allen, Nancy A.; Rodriguez-Gonzales, Bruno; Iacob, Eli; Greenwood, Deborah A.
Background: Previous research has identified that people with type 2 diabetes (T2D) within the Hispanic community would benefit from an online peer support community (OPSC) and continuous glucose monitoring (CGM) data to facilitate diabetes self-management. Methods: A mixed-methods feasibility study enrolled Hispanic, Spanish-speaking adults with T2D, not on insulin. Participants were provided with CGM and access to an OPSC for 12 weeks. Feasibility was assessed by number of eligible participants who enrolled, attrition, quantity of CGM data, validated clinical measures of self-efficacy, quality of life and adverse events. Engagement in the OPSC was measured using objective metrics on the online platform. Qualitative interviews were conducted upon conclusion of the intervention to assess feasibility, acceptability, participant satisfaction, and key recommendations for improvement. Results: Of 46 participants screened, 39 were eligible and 26 completed the study. Participants significantly improved self-efficacy scores. Posts in the OPSC related to goal setting had the highest engagement followed by mid-week and end of week check-in posts respectively. Participant interviews described challenges accessing the OPSC platform as a barrier to engagement. Despite this, all participants were satisfied with the intervention. Key recommendations for improvement included providing greater variety of and individualized education and the use of a peer support platform that is easily accessible. Conclusions: The CGM + OPSC intervention tailored to the Hispanic community with T2D was feasible, acceptable and satisfactory and improved participant self-efficacy for diabetes management which may lead to improved clinical outcomes.